VD_FINDINFO Jug / 2012 / 339 vom 13. Juli 2012 - VD Tribunal cantonal (2012)
ACTE D'ORDRE SEXUEL AVEC UNE PERSONNE DÉPENDANTE | 105 CP, 106 CP, 191 CP, 34 CP, 42 al. 1 CP, 42 al. 4 CP, 42 CP, 44 CP, 47 CP, 49 al. 2 CP